Peripheral neuropathy: an important contributor to physical limitation and morbidity in stages 3 and 4 chronic kidney disease. Issue 4 (12th February 2021) - Arnold, Ria; Pianta, Timothy J; Issar, Tushar; Kirby, Adrienne; Scales, Caoimhe M K; Kwai, Natalie C G; Endre, Zoltan; Krishnan, Arun V
Abstract: Background: Impaired physical function drives adverse outcomes in chronic kidney disease (CKD). Peripheral neuropathy is highly prevalent in CKD, though its contribution to physical function in CKD patients is unknown. This study examined the relationships between peripheral neuropathy, walking speed and quality of life (QoL) in stages 3 and 4 CKD. Methods: This was a prospective observational study investigating neuropathy in CKD patients with an estimated glomerular filtration rate (eGFR) 15–60 mL/min/1.73 m 2 . A total of 109 patients were consecutively recruited. The presence and severity of peripheral neuropathy was determined using the total neuropathy score. Walking speed was assessed at both usual and maximal speed, and QoL was assessed using the Short- Form 36 (SF-36) questionnaire. Results: Peripheral neuropathy was highly prevalent: 40% demonstrated mild neuropathy and 37% had moderate–severe neuropathy. Increasing neuropathy severity was the primary predictor of reduced walking speed ( R 2 = −0.41, P < 0.001) and remained so after multivariable analysis adjustment for diabetes. This association was evident for both usual and maximal walking speeds. Neuropathy correlated significantly with low scores on multiple domains of SF-36 including physical function ( r = −0.570, P < 0.001). Subanalysis according to diabetic status revealed a high prevalence of neuropathy both with and without diabetes; relationships to walking speed remained evident in subgroup analysis. However, those with diabetes demonstrated greater severity of neuropathy, slower walking speed and lower scores in QoL. Conclusions: Moderate to severe peripheral neuropathy was common in stages 3 and 4 CKD, associated with reduced walking speed independent of diabetes status and was correlated with patient-reported QoL. This suggests that neuropathy is an important contributor to declining physical function in CKD irrespective of diabetes status. Targeted diagnosis and management of peripheral neuropathy during CKD progression may improve functional outcomes and QoL. Graphical Abstract: